The Oxford handbook of Africa and economics. Volume 2, Policies and practices - e; Lin, Justin Yifu, 1952- (Oxford : Oxford University Press, 2015)
This volume aims at reassessing the economic policies and practices observed across the African continent since independence. It offers a collection of analyses by some of the leading economists and development thinkers of our time, and reflects a wide range of perspectives and viewpoints - even on the same topic. Africa's emergence as a potential economic powerhouse in the years and decades ahead amply justifies the scope and ambition of the book.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on September 8, 2015).
Keywords: Economics -- Africa; Africa -- Economic conditions; Africa -- Economic policy